Differential roles of normal and lung cancer-associated fibroblasts in microvascular network formation - Naveen R. Natesh; Pankaj Mogha; Alan Chen; Scott J. Antonia; Shyni Varghese (APL Bioengineering, 2024)
Perfusable microvascular networks offer promising three-dimensional in vitro models to study normal and compromised vascular tissues as well as phenomena such as cancer cell metastasis. Engineering of these microvascular networks generally involves the use of endothelial cells stabilized by fibroblasts to generate robust and stable vasculature. However, fibroblasts are highly heterogenous and may contribute variably to the microvascular structure. Here, we study the effect of normal and cancer-associated lung fibroblasts on the formation and function of perfusable microvascular networks. We examine the influence of cancer-associated fibroblasts on microvascular networks when cultured in direct (juxtacrine) and indirect (paracrine) contacts with endothelial cells, discovering a generative inhibition of microvasculature in juxtacrine co-cultures and a functional inhibition in paracrine co-cultures. Furthermore, we probed the secreted factors differential between cancer-associated fibroblasts and normal human lung fibroblasts, identifying several cytokines putatively influencing the resulting microvasculature morphology and functionality. These findings suggest the potential contribution of cancer-associated fibroblasts in aberrant microvasculature associated with tumors and the plausible application of such in vitro platforms in identifying new therapeutic targets and/or agents that can prevent formation of aberrant vascular structures.